Anterior cruciate ligament rehabilitation and return to sport in rock climbing athletes: a practical concept paper - Vagy, Jared; Schöffl, Volker; Ohde, Julia; Petersen, Wolf; Lutter, Christoph (Frontiers in Sports and Active Living, 2025)
Background: Acute ACL tears are becoming increasingly common among rock climbing athletes, particularly those who engage in bouldering. Hypothesis/purpose: The purpose of the paper was to develop a rehabilitation and return to sport protocol for rock climbing athletes after an anterior cruciate ligament reconstruction. Study design: The protocol is designed in 6 phases and emphasizes the importance of sport-specific postoperative rehabilitation protocols that address the unique needs of rock climbing athletes and stresses the need for sport-specific training prior to returning to full activity. Methods: The proposed rehabilitation protocol follows the stages of typical postoperative ACL protocols but with an emphasis on climbing-specific demands, such as eccentric landing mechanics and penduluming into a wall during lead climbing. Results: Climbers will be able to utilize the protocol to return to rock climbing. Conclusion: This paper highlights the need for further research on the topic and provides a foundation for future studies examining ACL tears in climbing athletes.
CRIS-Team Scopus Importer:2025-10-24
Keywords: ACL; bouldering; protocol; return to sport; rock climbing